Determination of Concentration of Copper and Zinc in Agricultural Land by Flame Atomic Absorption Spectrophotometry (F-AAS) - Phan, ThI Oanh; Vu, Anh Tuan; Tran, Thi Thuy; Tran, Quang Tung (Old Journal, 2018)
Method flame atomic absorption spectrophotometry (F-AAS) is used to determine the concentration of copper and zinc in agricultural land samples. The sample is treated with aqua regia. Method validation is performed by parameters such as linearity, LOD, LOQ, accuracy and trueness. The linear range is 0 – 7 ppm for Cu and 0 – 5 ppm for Zn on the Calibration curve with a correlation coefficient R2 ~ 0.99. The corresponding LOD and LOQ values of Cu were 0.019 and 0.062 ppm and of Zn were 0.021 and 0.066 ppm. The concentration of Cu and Zn in the 5 agricultural land samples was determined actually within the limits of the Ministry of Natural Resources and Environmen.